Increased durability of concrete made with fine recycled concrete aggregates using superplasticizers - Cartuxo, Francisco (2017)
This paper evaluates the influence of two superplasticizers (SP) on the durability properties of concrete made with fine recycled concrete aggregate (FRCA). For this purpose, three families of concrete were tested: concrete without SP, concrete made with a regular superplasticizer and concrete made with a high-performance superplasticizer. Five volumetric replacement ratios of natural sand by FRCA were tested: 0%, 10%, 30%, 50% and 100%. Two natural gravels were used as coarse aggregates. All mixes had the same particle size distribution, cement content and amount of superplasticizer. The w/c ratio was calibrated to obtain similar slump. The results showed that the incorporation of FRCA increased the water absorption by immersion, the water absorption by capillary action, the carbonation depth and the chloride migration coefficient, while the use of superplasticizers highly improved these properties. The incorporation of FRCA jeopardized the SP's effectiveness. This research demonstrated that, from a durability point of view, the simultaneous incorporation of FRCA and high-performance SP is a viable sustainable solution for structural concrete production.